First, multiply the second equation by 9 to make the coefficients of x the same:
9(x + 3y) = 9(-24)
9x + 27y = -216
Now, we have the system of equations:
9x - 7y = 22
9x + 27y = -216
Add the two equations together to eliminate x:
(9x - 7y) + (9x + 27y) = 22 - 216
18x + 20y = -194
Now, divide by 2 to simplify:
9x + 10y = -97
Now we have two equations:
9x - 7y = 22
9x + 10y = -97
Add these equations together to eliminate x:
(9x - 7y) + (9x + 10y) = 22 - 97
18x + 3y = -75
Divide by 3 to simplify:
6x + y = -25
Now, we have the equations:
6x + y = -25
9x - 7y = 22
Multiplying the first equation by 7 and the second equation by 1, we get:
42x + 7y = -175
9x - 7y = 22
Adding these equations together:
51x = -153
x = -3
Substitute x = -3 into one of the original equations:
x + 3y = -24
-3 + 3y = -24
3y = -21
y = -7
Therefore, the solution is (x, y) = (-3, -7).
Use the elimination method to solve the follow system of equations.
9x−7y=22
x+3y=−24
This question requires you to show your work.
(1 point)
Responses
(0,−8)
open paren 0 comma negative 8 close paren
(−3,−7)
open paren negative 3 comma negative 7 close paren
(4, 2)
(4, 2)
(3,−9)
1 answer